Professor Turun Padang's ‘Learn English Outdoor’ combines language skills and environmental awareness in Kuala Krau - Hafizoah, Kassim; Fatimah, Ali; Mohd Aizat, Zulkifli (UMPSA, 2024)
KUALA KRAU, 11 October 2024 – In a creative and impactful approach to language instruction, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), in collaboration with the Centre for Industry and Community Network (ICoN) and Centre for Corporate Communication organised a corporate social responsibility (CSR) programme under the ‘Professor Turun Padang’ (PTP) initiative.